The Effect on Financial Literacy, Intrinsic Motivation, ICT Knowledge, and Government Stimulus on the Readiness for Digitalization of Micro and Small Enterprises in Sumenep Regency - Ningsih, Reta Adistia; Asyari, Muhammad Asim (Sebatik, 2024)
The purpose of this study is to examine the effect of independent variables—namely financial literacy, intrinsic motivation, ICT knowledge, and government stimulus—on the dependent variable of digitalization readiness among micro and small enterprises. This study employs a quantitative method using multiple linear regression analysis with the assistance of SPSS version 25. The population consists of micro and small business owners in Sumenep Regency. The sample was determined using the purposive sampling technique, which involves selecting samples based on specific criteria and considerations. Only samples meeting these criteria were processed for analysis. The findings reveal that financial literacy does not significantly influence the digitalization readiness of micro and small enterprises. Similarly, intrinsic motivation does not significantly affect digitalization readiness. However, ICT knowledge has a positive and significant effect on digitalization readiness, and government stimulus also positively influences the digitalization readiness of micro and small enterprises.